Analisis Efektivitas Bantuan Orphan Kafala Baitulmal Muamalat Terhadap Pembangunan Sosial Ekonomi Anak Yatim di Aceh - Anis Kurlillah; Munadiati; Fadillah Bt Mansor; Iskandar (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
Aqad kafala is one of the popular forms of aqad in the empowerment of orphans being implemented today. This aqad has been implemented by OIC and IDB in the empowerment of orphans affected by conflict and tsunami in Aceh. The implementation of Aqad kafala is in the form of guaranteeing the fulfillment of the daily social and economic needs of orphans. The distribution of aid is carried out by cooperating with local NGOs, namely Baitulmal Muamalat, Rumah Zakat, and PKPU. This assistance has been started since 2006 until the end of 2022 with the number of orphans reaching 4100 orphans. The objective of this study is to analyze the effectiveness of the distribution of Orphan Kafala-OIC Alliance Aid to the development of the social and economic life of Aceh orphans. This study is using a qualitative research method. The data has been collected from the orphans who are being under the responsibility of Baitulmal Muamalat Indonesia. The data collection technique was through a questionnaire study. The results of this study showed that the kafala assistance given to the orphans in Aceh has provided a positive effect although not significant for the social and economic development of orphan families in Aceh.